The Relationship Between Student’s Interest in Learning English And Their Speaking Ability at Muq Langsa - Nadia Riski Lestari (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2020)
This research was conducted to investigate the relationship between students’ interest in learning English and their Speaking Ability. Interest is a tendency that the people know things or love some activities. Then, learning English is the important aspect to communication. The objective of study was to find out the relationship students’ interest in learning English and the impact of students’ interest in learning English. This research used qualitative research with descriptive design. The number of subjects were 15 students and only one teacher as informant. The research instrument was observation and interview. The result of research based on the researcher interview and observation, the researcher found that there is relationship between students’ interest in learning English and their speaking ability at the second-grade students at MUQ Langsa. The reason of students’ interest in learning English would like to try practice every time and also mastery speaking skill were important for students. Furthermore, there were impact of students’ interest in learning English for their speaking. It can be concluded that the relationship of students’ interest in learning English gave impact for students speaking ability.